Interactive E-Book on Improving Health Promotion Students' Communication Skills when They Offer Community Counseling - Made Dewi Sariyani; Ni Luh Seri Astuti; Kadek Sri Ariyanti; Rai Riska Resty Wasita; Gusti Ayu Mutiara Kharismayani (Universitas Pendidikan Ganesha, 2025)
The low communication skills of health promotion students in providing counseling to the community are characterized by a lack of self-confidence, limited ability to formulate health messages, and the predominance of conventional lecture-based learning methods. This study aims to develop an interactive e-book as a learning medium to enhance students’ communication skills in health promotion activities. The research employed a Research and Development (R&D) method adapted from the Behaviour Centre Design model. The study involved 11 health promotion students selected through purposive sampling. Data were collected through in-depth interviews, observations, and expert validation instruments for content and media. Data analysis was conducted qualitatively using a source triangulation approach to ensure validity. The results indicate that the interactive e-book is highly suitable for students’ needs, effectively improves their confidence, motivation, and communication skills, and is well received by both lecturers and students. The study implies that the interactive e-book can serve as an innovative learning medium relevant to the health promotion curriculum while preparing students to become more capable agents of change in raising community awareness and promoting healthy living behaviors.